2015
DOI: 10.1107/s1600576715014740
|View full text |Cite
|
Sign up to set email alerts
|

Reliably distinguishing protein nanocrystals from amorphous precipitate by means of depolarized dynamic light scattering

Abstract: Crystallization of biological macromolecules such as proteins implies several prerequisites, for example, the presence of one or more initial nuclei, sufficient amounts of the crystallizing substance and the chemical potential to provide the free energy needed to force the process. The initiation of a crystallization process itself is a stochastic event, forming symmetrically assembled nuclei over kinetically preferred protein‐dense liquid clusters. The presence of a spatial repetitive orientation of macromole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…homogenous and non-aggregated) sample is ideal for crystallization 85 . In addition, DLS is also used in SFX experiments to determine nanocrystal size distribution and homogeneity across multiple conditions 86 . DLS measures the light scattered by particles in solution.…”
Section: Nanocrystallization and Characterizationmentioning
confidence: 99%
“…homogenous and non-aggregated) sample is ideal for crystallization 85 . In addition, DLS is also used in SFX experiments to determine nanocrystal size distribution and homogeneity across multiple conditions 86 . DLS measures the light scattered by particles in solution.…”
Section: Nanocrystallization and Characterizationmentioning
confidence: 99%
“…Furthermore, the 3D response surface model for DDLS signals showed an intensity higher than 150 kHz at 16% of PEG8k 9 minutes after initiation of the reaction, which characterizes the presence of a periodic structure in the ConA clusters (Figure 2e). Previous studies describing real-time monitoring of lysozyme, thioredoxin, and thaumatin crystal nucleation, applying simultaneous DLS/DDLS measurements, also describe changes in the polarization plane of the scattered light (DDLS signals up to 150 kHz) and confirmed-after verification by powder diffraction and scanning electron microscopy-the presence of crystalline lattices [43]. Thus, the volume fraction conferred by 16% PEG8k corresponds to the boundary line located between ConA clusters and the crystalline phase.…”
Section: Discussionmentioning
confidence: 71%
“…The DLS/DDLS instrument (XtalConcepts GmbH, 22525 Hamburg, Germany) was described previously by Schubert et al in 2015 [43]. The autocorrelation functions (ACF) obtained for all assays were analyzed by applying the CONTIN algorithm [44] and the decay time constants of the DLS (translation diffusion, D t ) and DDLS data (rotational diffusion, D r ) were calculated independently via the Stokes−Einstein and Stokes−Einstein−Debye equations [43], respectively. The viscosity was considered and adjusted according to the percentage of CA solutions in all assays (Table 1) and the actual hydrodynamic radius was calculated accordingly.…”
Section: Dynamic Light Scattering (Dls) and Depolarized Dynamic Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been used to identify microcrystals with homogenous physical properties. Such methods include dynamic light scattering (Schubert, 2015), second-order nonlinear imaging of chiral crystals (Luft, 2015), as well as microfluidic technologies (Abdallah et al, 2015; Kupitz et al, 2014) and transmission electron microscopy (TEM) (Gomery et al, 2013; Redecke et al, 2013; Stevenson et al, 2014b). In the latter case, we previously showed that not only is TEM capable of identifying conditions amenable to microcrystal formation, but also is capable of characterizing the intrinsic properties of the microcrystals (I.E.…”
Section: Introductionmentioning
confidence: 99%